Development and functional assessment of natural latex membranes : a new proposal for the treatment of amblyopia - Ribeiro, Jaqueline Alves (2016)
Tese (doutorado)—Universidade de Brasília, Faculdade de Tecnologia, Departamento de Engenharia Elétrica, 2016.